THE RELATIONSHIP OF MAKING AUDIO VISUAL MEDIA WITH STUDY MOTIVATION IN PSYCHOLOGICAL COURSES: HUBUNGAN PEMBUATAN MEDIA AUDIO VISUAL DENGAN MOTIVASI BELAJAR PADA MATA KULIAH PSIKOLOGI - Nunik Esti Utami; Saifullah; Eka Jaya Putera Utama; Basuki Wibowo (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2020)
Learning that is carried out by students is using the cooperative learning model by making creative media to support the percentage of students in the classroom. Some students do not understand in making Audio Visual learning media, by using audio visual media it is expected that student learning motivation will arise. Quantitative descriptive method is used when it aims to describe or explain events or an incident that is happening at the present time in the form of meaningful numbers. With a number of subjects of 26 students. Interlationsship studies. Testing for normality uses the Kolmogorov-Smirnov analysis technique and for calculations using the SPSS 16.0 for Windows program. The data is said to be normally distributed if the significance value is greater than 0.05 at the significance level α = 0.05. The linearity results above indicate that the significance level is 0.588> 0.05; so that the two variables can be said to be linear. Based on the results of the hypothesis is the hypothesis in this study is "There is a positive and significant relationship between learning motivation and the making of audio-visual media by students in the subject of educational psychology. 4.243> 0.555) and a significance value of 0.000, which means less than 0.05 (0.000 <0.05). Based on these results, the first hypothesis in this study was not rejected. The results of the product moment correlation analysis showed that there was a positive and significant relationship between learning motivation and the making of audio-visual media by students in educational psychology subjects. there is a relationship between the making of Audio Visual media in the educational psychology course with student learning motivation in the educational psychology course.